Peran Coffee Shop Dalam Menunjang Minat Belajar Di Luar Kampus Bagi Mahasiswa Universitas Pamulang, Tangerang Selatan - Raka Dwi Ramadhoni; Eva Solina; Firka Cantika Aulia Putri (PT PUSTAKA CENDEKIA GROUP, 2024)
Coffeeshops have become an important alternative space for student learning, especially for Universitas Pamulang students in Tangerang Selatan. This study aims to identify the role of coffeeshops in supporting students' motivation to study outside of campus and the factors that make coffeeshops a popular choice for academic activities. Using a qualitative approach with observations and interviews with students who frequently study in coffeeshops, this study found that a comfortable atmosphere, adequate internet access, and supporting facilities are key attractions for students. Additionally, coffeeshops provide a conducive space for group discussions, collaborative tasks, and individual assignments. The results show that coffeeshops serve as an alternative study space that boosts student motivation and productivity in completing academic activities outside of campus. Recommendations from this study can guide coffeeshop management in enhancing facilities that support student learning activities.